Estimativa do esgoto doméstico ao longo do Igarapé do Mindu, em Manaus-AM - Paiva, Carlos Estevão Lúcio de (Brasil, 2022)
The city of Manaus had a horizontal and partially disordered growth, intensified after the implementation of the Manaus Free Trade Zone, around the end of the ´60s. Despite some initiatives by the Government, the occupations took place irregularly, as a consequence of that, basic sanitation services were neglected, especially regarding to the sanitary sewage service, which according to AGEMAN (2022) covers only 25% of the population. Considering this scenario, and understanding the relevance of the Igarapé do Mindu at the municipal level, a design study was carried out for the collection of domestic sewage in this sub-basins and its areas using the CIVIL3D software. Along with that, a survey of population data was carried out to study the population projection, in order to estimate the volume of sewage in each sub-basin. Therefore, this work can guide the implementation of the sewage system in this area and, consequently, promote improvements in the quality of life and health of the population, through the depollution of the streams.